PELATIHAN DESAIN GRAFIS BERBASIS VECTOR DAN BITMAP MENGGUNAKAN APLIKASI CORELDRAW DI SMK NASIONAL PADANG - Yulia, Yulia; Arnomo, Sasa Ani; Karnadi, Very (PUAN INDONESIA, 2024)
CorelDraw is a computer program that edits vector lines. CorelDraw is used to process images for work such as in the field of publication or printing that requires a visualization process. Many entrepreneurs are involved in this field, even as a business sector to open a business. Padang National Vocational School is one of the Padang National Vocational Schools which is quite famous in the city of Batam. Padang National Vocational School has four study programs, one of which is related to the field of computers, namely Computer and Network Technology. The problem that occurs is that the student recognizes and knows enough about CorelDraw, but in terms of learning, the student is quite difficult because they only learn the basic parts in learning, and the CorelDraw application itself is not really applied, while in the CorelDraw subject there is this material. So, in the field of design, students experience a little difficulty, they only know the CorelDraw application but don't apply it enough.